1981
DOI: 10.1126/science.7280692
|View full text |Cite
|
Sign up to set email alerts
|

Gonadal Hormones Induce Dendritic Growth in the Adult Avian Brain

Abstract: Ovariectomized adult female canaries were treated with physiological doses of testosterone, dihydrotestosterone, or estradiol. Singing, which is typical of males, occurred in the testosterone-treated birds but not in any of the other birds. The effect of these hormones was assessed on dendrites from a class of neurons in the nucleus robustus archistriatalis (RA), a forebrain nucleus for song control. The RA neurons of the testosterone-treated birds had dendritic trees resembling those of intact males. The RA n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
130
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 374 publications
(142 citation statements)
references
References 28 publications
11
130
0
Order By: Relevance
“…In birds, we know that testosterone (T) and its metabolites, E 2 and 5α-dihydrotestosterone (DHT), influence the anatomy of the vocal control circuit in adult songbird species (DeVoogd & Nottebohm, 1981;Schlinger, 1997;Tramontin & Brenowitz, 2000). In addition, E 2 appears to regulate apoptosis after Hp damage in the zebra finch (Saldanha, Rohmann, Coomaralingam, & Wynne, 2004).…”
Section: Hormones and Hpmentioning
confidence: 99%
“…In birds, we know that testosterone (T) and its metabolites, E 2 and 5α-dihydrotestosterone (DHT), influence the anatomy of the vocal control circuit in adult songbird species (DeVoogd & Nottebohm, 1981;Schlinger, 1997;Tramontin & Brenowitz, 2000). In addition, E 2 appears to regulate apoptosis after Hp damage in the zebra finch (Saldanha, Rohmann, Coomaralingam, & Wynne, 2004).…”
Section: Hormones and Hpmentioning
confidence: 99%
“…Administration of T, or its metabolite E 2 , increases neuronal number and size in HVC and Area X in song sparrows, white-crowned sparrows (Zonotrichia leucophrys gambelii), and darkeyed juncos (Junco hyemalis), and increases neuron size in RA (Gulledge & Deviche, 1995;Tramontin et al, 2003;Soma et al, 2004). The arborization of neurons within RA is profoundly affected by E 2 in the adult canary, with the number of dendrites and synaptic profiles increasing with steroid administration (DeVoogd & Nottebohm, 1981). Surprisingly, the steroidal influence on the song system can be extremely rapid, as significant increases in HVC neuron number are detectable within a week of T administration (Brenowitz, 2004).…”
Section: Seasonal Adult Neuroplasticity In the Song Systemmentioning
confidence: 99%
“…Many studies have shown that variations in gonadal hormones in female animals -in particular estrogen-lead to structural brain changes, and to changes in behavior (Darnaudéry et al, 2007;DeVoogd & Nottebohm, 1981;Fader, Hendricson, & Dohanich, 1998;Galea & Kavaliers, 1995;Galea et al, 2000;Gibbs, 2000;Korol, 2004;Luine & Frankfurt, 2012;Pawluski, Brummelte, Barha, Crozier, & Galea, 2009;Woolley, 1998;Woolley & McEwen, 1993). Endogenous estrogen fluctuates naturally during the estrous cycle, peaks during pregnancy, and declines at menopause.…”
Section: Introductionmentioning
confidence: 99%